God's word to Israel - Jensen, Joseph, 1924- (Collegeville, Minnesota, Liturgical Press Academic, 2021)
"In this completely revised and expanded edition of God's Word to Israel Joseph Jensen incorporates the latest scholarship using a combination of the historical, literary, and thematic approaches to present a unified treatment of the Old Testament"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Introductions; Introductions